Denmark : 2021 Article IV Consultation-Press Release; Staff Report; and Staff Supplement. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2021)
Denmark entered the pandemic on a strong economic footing and utilized its large policy space built over time to successfully address the crisis and lay the ground for a strong recovery. The outlook is for a rebound in activity, but uncertainty remains elevated with risks tilted to the downside. Macrofinancial vulnerabilities persist as housing price growth has accelerated and household debt remains high. The current account declined but remains in surplus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Denmark